LEGAL RELATIONS REGARDING INTERNATIONAL CREDIT AND SETTLEMENTS (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article delves into the complex legal landscape surrounding international credit and settlements, exploring the various aspects that govern these transactions. Through a thorough literature analysis, the article examines existing legal frameworks, methodologies, and results pertinent to international credit and settlements. The discussion highlights the challenges, nuances, and emerging trends in this domain, offering valuable insights for policymakers, legal practitioners, and businesses engaged in cross-border transactions.